Opportunities for Digital Financial Services in the Cocoa Value Chain in Côte d’Ivoire : Insights from New Data - Lonie, Susie; Martinez, Meritxell; Oulai, Rita; Tullis, Christopher (World Bank, Washington, DC, 2018)
Côte d’Ivoire has the world’s largest cocoa sector, producing over 1.4 million metric tons of raw cocoa per year, accounting for thirty two percent of world production. Harvest payments often arrive late due to the complex logistics of cash-based payments and, it is not uncommon for the amount farmers receive to be somewhat below market value due to high commissions taken by chains of intermediary middlemen. Cognizant of these costs and inefficiencies, many actors in the cocoa value chain are exploring alternatives. One such alternative is paying farmers through Digital financial services (DFS). This research focuses specifically on mobile money accounts and discusses, first, how these have already expanded financial inclusion in Côte d’Ivoire and, secondly, how mobile money could help deliver products to cocoa farmers that meet their needs. The study is a knowledge product of the Partnership for Financial Inclusion, a joint initiative of IFC and The MasterCard Foundation to expand microfinance and advance digital financial services in Sub-Saharan Africa. It is organized as follows: The first section reviews the financial inclusion landscape in Côte d’Ivoire, revealing that DFS has unusually high penetration in rural areas. The second section analyzes the specific financial behavior of cocoa farmers based on new data collected by IFC,and is followed by a third section presenting a framework for how DFS could help improve farmers’ lives. The report concludes with a call to stakeholders to keep piloting and innovating with products and payment channels that cater to the financial needs of rural communities in Côte d’Ivoire and beyond.